Evaluation of saponin loaded gellan gum hydrogel scaffold for cartilage regeneration - Jeon, H. Y. (2018)
Several concentrations of saponin (Sa), which is water-soluble, were fabricated well with gellan gum (GG) solution. Sa, found in many plants like clematis and ginseng, has long been used in traditional chinese medicine to treat joint diseases including osteoarthritis. Also it has its ability of anti-inflammatory, antioxidant and anti-cancer. GG hydrogel is suitable as a cell encapsulating agent in the field of cartilage regeneration because of its easy processing and biocompatibility. In this study, GG hydrogel scaffolds with different concentration of Sa were conducted for analysis by SEM, FT-IR, compressive strength, water uptake, degradation rate, MTT assay, mRNA expression. It was observed that 0.025 wt% Sa/GG hydrogel scaffold shows good morphology, cell proliferation and mRNA expression results. The composite material supports cell growth covered with extracellular matrix (ECM) with maintaining its function. As a result, incorporation of Sa loaded with GG hydrogel scaffolds had positive result up to 0.025 wt% in cartilage regeneration.